STRATEGY TO INCREASE COMMUNITY INCOME THROUGH DISHWASHING SOAP TRAINING IN KUALA TERUSAN VILLAGE, RIAU PROVINCE - Rahmiatul Aula; Raudhatinur; Almunadiya; Intan Maulida; Yusnidar; Venna Maulida Mustika (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
A strategy to increase community income through dishwashing soap training in Kuala Terusan Village, Pangkalan Kerinci District, aimed to increase community income, particularly for housewives, by utilizing dishwashing soap production as a source of additional income. The strategy for participating in this training and implementing this activity was motivated by the economic conditions of the community, which largely relies on fishing for a living, necessitating alternative businesses that could supplement family income. The strategy for participating in this dishwashing soap training included outreach, practical training in making liquid dishwashing soap, and assistance with product packaging. The results of the activity showed that the community was very enthusiastic about the information provided regarding business opportunities through dishwashing soap production. Furthermore, the community was able to understand the stages of soap production comprehensively. This activity not only provided new skills but also encouraged entrepreneurial spirit and increased public awareness of the importance of creativity in increasing household income.